Vitamin D and the athlete–patient: state of the art. Issue 1 (13th November 2020) - Ribbans, William J; Aujla, Randeep; Dalton, Seamus; Nunley, James A
Abstract : Vitamin D deficiency is common in athletes. The conventional measurement of vitamin D levels provides a general indicator of body stores. However, there are nuances in its interpretation as values of 25(OH)D do not correlate absolutely with the amount of 'bioavailable' vitamin to the cells. Vitamin D should be regarded as a hormone and influences between 5% and 10% of our total genome. Determining the precise effect of the vitamin, isolated from the actions of other cofactors, is not straightforward and restricts our complete understanding of all of its actions. Deficiency has harmful effects on not only bone and muscle but also wider areas, including immunity and respiratory and neurological activities. More caution should be applied regarding the ability of supranormal vitamin D levels to elevate athletic performance. Hopefully, future research will shed more light on optimal levels of vitamin D and supplementation regimes, and improved understanding of its intracellular control of our genetic mechanisms and how extrinsic influences modify its activity.